Kesalahan Berbahasa dalam Laporan Keuangan dan Dampaknya terhadap Kualitas Informasi: Penelitian - Yenni Riski Mutia Sihotang; Nasratul Mila; Salsabiilah Dwi Amanda; Nadiya Salsabila Herman; Roland Imawan; Putra Hadiwinata; Muhammad Anggie Januarsyah Daulay (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to identity language errors in accounting student’s financial reports and examine their impact on the quality of information. The research employed a descriptive qualitative method with document analysis of 15 financial reports prepared by students. The results revealed that the most frequent errors occurred in the use of accounting terminology, spelling, and sentence structure. These errors affected the clarity, readability, and accuracy of the information, which may lead to misinterpretation by report users. The study concludes that that linguistic accuracy plays a crucial role in maintaining the quality of financial information. Therefore, language